If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(t + 6) = 18 Reorder the terms: -9(6 + t) = 18 (6 * -9 + t * -9) = 18 (-54 + -9t) = 18 Solving -54 + -9t = 18 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '54' to each side of the equation. -54 + 54 + -9t = 18 + 54 Combine like terms: -54 + 54 = 0 0 + -9t = 18 + 54 -9t = 18 + 54 Combine like terms: 18 + 54 = 72 -9t = 72 Divide each side by '-9'. t = -8 Simplifying t = -8
| f(x)=20+40 | | 4x=18x | | -2(3t-5)+3t=2t-2 | | 6(x+36)-3(2x+12)=4x-10 | | x^2-14y=0 | | 5b-b=8 | | 3x(5-2x)+4=6 | | 7/12=7/9x | | (1-3x)=-8x+14 | | 2/n=-7 | | 20=a+3 | | x^2=-5y | | 8(x-4)+4(x-8)+(x-3)=2x-1 | | 66+6y-20=16y-10-2y | | Z^3+5z+3z^2+1+4-2z^2= | | 24/25=s/35 | | -10/9i | | 4(n+6)=8-4(n-2) | | 12+p=8+7 | | =x^2+4x | | 2(cos(2pi))=0 | | 4m^5n^0(5m^3)= | | 2/7x234/1 | | 4(2x+-1)=.5(16x+-8) | | ln(3x-2)=2.3 | | 3xwhat=123 | | 12y+10y=20y-3 | | 3(n+8)=3-3(n-7) | | 12+9y=9 | | 17-5x=35 | | 3xa=123 | | 12y+10y=20y-60 |